Physical, chemical, and biological treatment of chemical waste from teaching laboratories at Universidad Nacional, Costa Rica - Rodríguez-Rodríguez, Jorengeth Abad (2020)
Herein, we report the physical, chemical, and biological treatment of wastewater generated in the teaching laboratories at Universidad Nacional, Costa Rica. Initial physicochemical treatment included neutralization and coagulation-flocculation, followed by a biological treatment with fungi (Aspergillus sp. and Penicillium dipodomyicola) or bacterias, the latter were isolated from the sludge from the campus’ wastewater treatment plant and the greywater collection tank at the School of Chemistry. The samples’ pH prior to treatment was ≤ 2, while COD ranged between 3000 and 30 000 mg/L. Gas chromatography-mass spectra analysis indicated the presence of 55 organic compounds in the wastewater, some of which reached undetectable concentrations after treatment. The fungi and the bacterial strain removed up to 50% of the substances, while the toxicity decreased with respect to time of exposure to the treatment. Results support the potential use of these microorganisms as bioremediators. Although the organic compounds were partially removed, the treated wastewater exhibited high toxicity for Daphnia magna (water flea). Further experiments with longer treatment times or other strains might be needed for effective removal of pollutants.